The neural signature of the Fraser illusion: an explorative EEG study on Fraser-like displays - Yun, Xuyan; Hazenberg, Simon J.; Jacobs, Richard H. A. H.; Qiu, Jiang; van Lier, Rob (Frontiers in Human Neuroscience, 2015)
We studied neural correlates accompanying the Fraser spiral illusion. The Fraser spiral illusion consists of twisted cords superimposed on a patchwork background arranged in concentric circles, which is typically perceived as a spiral. We tested four displays: the Fraser spiral illusion and three variants derived from it by orthogonally combining featural properties. In our stimuli, the shape of the cords comprised either concentric circles or a single spiral. The cords themselves consisted of black and white lines in parallel to the contour of the cords (i.e. parallel cords), or oblique line elements (i.e. twisted cords). The displays with twisted cords successfully induced illusory percepts, i.e. circles looked like spirals (the Fraser spiral illusion) and spirals looked like circles (i.e., a ‘reverse Fraser illusion’). We compared the event-related potentials in a Stimulus (Circle, Spiral) × Percept (Circle, Spiral) design. A significant main effect of Stimulus was found at the posterior scalp in an early component (P220-280) and a significant main effect of Percept was found over the anterior scalp in a later component (P350-450). Although the EEG data suggest stimulus-based processing in posterior area in an early time window and Percept based processing in the later time window, an overall clear-cut stimulus-percept segregation was not found due to additional interaction effects. Instead, the data, especially in the later time window in the anterior area, point at differential processing for the condition comprising circle shapes but spiral percepts (i.e. the Fraser illusion).